Efektivitas Model Pembelajaran Integratif untuk Peningkatan Literasi dan Numerasi Siswa Madrasah Ibtidaiyah di MI Ma’arif Trikarso Kabupaten Kebumen - Umam, Faiz Barohinul; Jannah, Fina Raudlatul; Hidayat, Taufik (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
This study aims to analyze the effectiveness of integrative learning model in improving students' literacy and numeracy in Madrasah Ibtidaiyah Ma'arif Trikarso, Kebumen Regency. The method used is qualitative with a descriptive approach, through interviews with the madrasah head, deputy head of curriculum, and students, as well as observation and documentation. The learning process is carried out based on four stages of management, namely planning, organizing, implementing, and supervising. The research results have several stages. In the planning stage, the full approach is applied by identifying relevant themes that integrate various subjects, using local context-based learning materials, and designing projects across subject areas. The organizing stage involves forming cross-subject teaching teams and providing supporting resources such as modules and integrative evaluation tools. During the implementation stage, the project-based method is applied, encouraging students to discuss, explore information and link concepts from various lessons. The supervision stage is conducted through classroom monitoring, evaluation of learning outcomes with integrative instruments, and reflection to improve learning strategies. The results show that the integrative learning model is effective in improving students' literacy and numeracy skills. However, this research is still limited to the effectiveness of learning integration without exploring the relationship between collaboration and motivation between teachers and students. Future research is expected to explore these aspects to support the success of learning more thoroughly